PERAN DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DPPKB) DALAM MENINGKATKAN PENCAPAIAN PESERTA KB PADA KAMPUNG KB DI KOTA KUPANG - Rocky Jhonson Napang Leo; Nursalam; Aspri Budi Oktavianto (PT. Saha Kreasi Indonesia, 2026)
The rapid population growth in Kupang City, particularly in Kampung KB of Lasiana Subdistrict, requires proper interventions to improve the quality of family life. This study aims to analyze the role of the Population and Family Planning Control Office (DPPKB) in increasing the participation of Family Planning (KB) participants in Kampung KB. Using a qualitative approach through a case study, this research explores the implementation of the KB program through counseling, service provision, and inter-sectoral coordination. The results show that DPPKB Kupang has successfully carried out its normative and actual roles in educating the public and providing equitable KB services. However, challenges remain in increasing the use of long-term contraceptive methods due to social stigma, limited information, and family support. The evaluation highlights the importance of a socio-cultural approach to enhance community participation. This study offers recommendations to strengthen inter-sectoral coordination and improve the distribution of KB information to achieve optimal family welfare goals.